Oligomeric and phosphorylated alpha-synuclein as potential CSF biomarkers for Parkinson’s disease - Nour K. Majbour (8809316) (2016)
Background Despite decades of intensive research, to date, there is no accepted diagnosis for Parkinson’s disease (PD) based on biochemical analysis of blood or CSF. However, neurodegeneration in the brains of PD patients begins several years before the manifestation of the clinical symptoms, pointing to serious flaw/limitations in this approach. Results To explore the potential use of alpha-synuclein (α-syn) species as candidate biomarkers for PD, we generated specific antibodies directed against wide array of α-syn species, namely total-, oligomeric- and phosphorylated-Ser129-α-syn (t-, o- and p-S129-α-syn). Next we sought to employ our antibodies to develop highly specific ELISA assays to quantify α-syn species in biological samples. Finally we verified the usefulness of our assays in CSF samples from 46 PD patients and 48 age-matched healthy controls. We also assessed the discriminating power of combining multiple CSF α-syn species with classical Alzheimer’s disease biomarkers. The combination of CSF o-/t-α-syn, p-S129-α-syn and p-tau provided the best fitting predictive model for discriminating PD patients from controls. Moreover, CSF o-α-syn levels correlated significantly with the severity of PD motor symptoms (r = -0.37). Conclusion Our new ELISA assays can serve as research tools to address the unmet need for reliable CSF biomarkers for PD and related disorders. Other Information Published in: Molecular Neurodegeneration License: https://creativecommons.org/licenses/by/4.0/   See article on publisher's website: https://dx.doi.org/10.1186/s13024-016-0072-9